Constitutive and inducible expression of SKALP/elafin provides anti-elastase defense in human epithelia. - Pfundt, R (1996)
Skin-derived antileukoproteinase (SKALP), also known as elafin, is a serine proteinase inhibitor first discovered in keratinocytes from hyperproliferative human epidermis. In addition to the proteinase inhibiting domain which is directed against polymorphonuclear leukocyte (PMN) derived enzymes such as elastase and proteinase 3, SKALP contains multiple transglutaminase (TGase) substrate domains which enable crosslinking to extracellular and cell envelope proteins. Here we show that SKALP is constitutively expressed in several epithelia that are continuously subjected to inflammatory stimuli, such as the oral cavity and the vagina where it co-localizes with type 1 TGase. All epithelia from sterile body cavities are negative for SKALP. In general, stratified squamous epithelia are positive, whereas pseudostratified epithelia, simple/glandular epithelia and normal epidermis are negative. SKALP was found in fetal tissues of the oral cavity from 17 wk gestation onwards where it continued to be expressed up to adult life. Remarkably, in fetal epidermis SKALP was found from week 28 onwards, but was downregulated to undetectable levels in neonatal skin within three months, suggesting a role during pregnancy in feto-maternal interactions or in the early maturation phase of the epidermis. Immunoelectron microscopy revealed the presence of SKALP in secretory vesicles including the lamellar granules. In culture models for epidermal keratinocytes we found that expression of the endogenous SKALP gene provided protection against cell detachment caused by purified elastase or activated PMNs. Addition of exogenous recombinant SKALP fully protected the keratinocytes against PMN-dependent detachment whereas superoxide dismutase and catalase were only marginally effective. These findings strongly suggest that the constitutive expression of SKALP in squamous epithelia, and the inducible expression in epidermis participate in the control of epithelial integrity, by inhibiting PMN derived proteinases.